Learning Innovation: The Impact of AI-Based Video Media in Improving the Skills of Adolescent Girls for Stunting Prevention - Hasbi Taobah Ramdani; Murtiningsih; Fauziah Rudhiati; Ida Maryati; Nunung Nurjanah (Postgraduate, University of Mataram, 2025)
This study examines the effect of Artificial Intelligence (AI)-based video media on improving adolescent girls’ skills in preventing stunting. A quantitative quasi-experimental design was applied using a pre-test–post-test approach with a control group. The intervention group received AI-based video learning, while the control group used ChatGPT-based text interaction. Results show a significant improvement in the intervention group, with a post-test mean score of 82.19 compared to 41.16 in the control group. The intervention group also demonstrated a narrower confidence interval (78.55–85.83), indicating higher consistency in skill acquisition, whereas the control group showed a wider range (36.27–46.05). These findings confirm that visual, structured, and AI-enhanced learning materials improve comprehension and practical skills more effectively than text-based interactions alone. The study reinforces the importance of integrating innovative digital media into health education programs. In conclusion, AI-based video media is a highly effective tool for strengthening adolescents’ stunting prevention skills and holds strong potential for broader implementation in early prevention strategies.